Evaluation of Optical See-Through Head-Mounted Displays in Training for Critical Care and Trauma - Azimi, Ehsan; Winkler, Alexander; Tucker, Emerson; Qian, Long; Sharma, Manyu; Doswell, Jayfus; Navab, Nassir; Kazanzides, Peter (2018 IEEE Conference on Virtual Reality and 3D User Interfaces (VR), 2018)
One major cause of preventable death is a lack of proper skills for providing critical care. Conventional training for advanced emergency medical procedures is often limited to a verbal block of instructions and/or an instructional video. In this study, we evaluate the benefits of using an optical see-through head-mounted display (OST-HMD) for training of caregivers in an emergency medical environment. A rich user interface was implemented that provides 3D visual aids including images, text and tracked 3D overlays for each task. A user study with 20 participants was conducted for two medical tasks, where each subject received conventional training for one task and HMD training for the other task. Our results indicate that using a mixed reality HMD is more engaging, improves the time-on-task, and increases the confidence level of users.